Contribuição para o conhecimento das doenças do grupo tifo exantemático do Brasil - Octavio de Magalhães (Memorias do Instituto Oswaldo Cruz, 1955)
In this work the author publishes an observation of a human case, which he believes to be the second in South America, of "Q" fever in Minas Gerais. The first positive data and the first observation were made in S. Paulo by Dr. Helvecio Brandão and there communicated to the S. Paulo Medical Association in 1951 and 1954. The first part was published in 1953; the second part is yet unpublished. The author of the present work cured his patient with Terramycine. He thinks that greater research should be made amongst the workpeople who have to do with cattle in the pastures and slaughterhouses in order to verify the extent of the disease amongst us. Belo Horizonte Dezembro de 1954